Groundwater recharge and wells : A guide to aquifer storage recovery - Pyne , R. David G. (LEWIS PUBLISHERS / Washington, 1995)
Contents: Introduction; ASP program development; Desing of ASR systems; Selected ASR technical Issues; Geochemistry; Selected Non-Technical Issues; Alternative ASR applications; Future direction; Selected case studies